Ethnobotany plants used by Ngaju Dayak tribe for COVID-19 therapeutic practices - Sunariyati, Siti; Krestina, Widya; Rohimah , Memi Fitri (Biological Environment and Pollution, 2024)
The Ngaju Dayak tribe in Kasongan, Katingan Regency, critically relies on traditional medicinal plants for health, including COVID-19 symptom management. Despite this reliance, crucial knowledge about these immunomodulatory plants remains largely undocumented, posing an urgent risk to their preservation and potential medical application. This study aimed to identify and document the specific plants utilized for COVID-19 treatment—before, during, and after the pandemic—detailing plant parts used, preparation methods, and cultural significance. Employing a mixed-method approach with structured interviews and snowball sampling in Kasongan, the research identified 15 plant species with therapeutic potential, including Peronema canescens, Orthosiphon stamineus, and Zingiber officinale. Leaves were the most frequently used plant part (68.5%), predominantly prepared by boiling (78.2%). Significantly, Peronema canescens emerged as the primary choice during the pandemic (70% fidelity level), while Annona muricata was prominent before and after. Peronema canescens also exhibited the highest Index of Cultural Significance (ICS) at 18. These findings highlight the dynamic ethnobotanical practices of the Ngaju Dayak tribe and underscore the urgent need for conservation and further scientific validation to leverage this traditional knowledge for broader health benefits and ensure community well-being.